The Risk Theory - Zusman Tinman, Susana (1980)
This article deals with the theory of risk in the context of contractual obligations, particularly in synallagmatic contracts, where the parties have reciprocal obligations. In this regard, the author examines how the impossibility of fulfilling an obligation due to an act of God, force majeure or absence of fault affects the correlative obligation. To address this, three historical solutions are presented: res perit creditori, res perit debitori, and res perit domino, which links risk to ownership. However, she questions the myth that "res perit domino" is an immutable  principle and analyzes its application in various legal systems and in the civil codes of Brazil and Argentina. Additionally, the text criticizes the inconsistency of the historical method of interpretation and proposes a detailed analysis of the evolution of legislation, including the treatment of the theory of risk in the Peruvian Civil Code, specifically article 1175. Regarding this, it discusses the attribution of risk according to the principles indicated and argues that the article 1175 doesn't solve the problem of assumption of risk in synallagmatic contracts, being reiterative and unnecessary. Finally, the author concludes that the article does not contemplate the theory of risk, nor does it incorporate the rule of "res perit domino", which underlies the materialistic position on the transfer of ownership of real estate, so that it could undermine it. It is therefore necessary that the civil legislation be revised to clarify the distribution of risks in these contractual situations.